SNAI transcription factors mediate epithelial–mesenchymal transition in lung fibrosis. Issue 12 (22nd October 2009) - Jayachandran, A; Königshoff, M; Yu, H; Rupniewska, E; Hecker, M; Klepetko, W; Seeger, W; Eickelberg, O
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is a fatal interstitial lung disease characterised by accumulation of activated (myo)fibroblasts and excessive extracellular matrix deposition. The enhanced accumulation of (myo)fibroblasts may be attributed, in part, to the process of transforming growth factor β1 (TGFβ1)-induced epithelial–mesenchymal transition (EMT), the phenotypic switching of epithelial to fibroblast-like cells. Although alveolar epithelial type II (ATII) cells have been shown to undergo EMT, the precise mediators and mechanisms remain to be resolved. The objective of this study is to investigate the role of SNAI transcription factors in the process of EMT and in IPF. Methods: Using quantitative reverse transcription-PCR (RT-PCR), immunofluorescence, immunohistochemistry, western blotting, as well as gain- and loss-of-function studies and functional assays, the role of SNAI1 and SNAI2 in TGFβ1-induced EMT in ATII cells in vitro was assessed; and the expression of SNAI transcription factors was analysed in experimental and human IPF in vivo. Results: TGFβ1 treatment increased the expression and nuclear accumulation of SNAI1 and SNAI2, in concert with induction of EMT in ATII cells. SNAI overexpression was sufficient to induce EMT, and small interfering RNA (siRNA)-mediated SNAI depletion attenuated TGFβ1-induced ATII cell migration and EMT. SNAI expression was elevated in experimental and human IPF and localised to hyperplastic ATII cells in vivo. Conclusions: The results demonstrate that TGFβ1-induced EMT in ATII cells is essentially controlled by the expression and nuclear translocation of SNAI transcription factors. Increased SNAI1 and SNAI2 expression in experimental and human IPF in vivo suggests that SNAI-mediated EMT may contribute to the fibroblast pool in idiopathic pulmonary fibrosis.